Ka Bakau: Ekowisata Mangrove Berbasis Pengetahuan Lokal - Septian Yuda Pratama; M. Rawa El Amady; Achmad Hidir (Lasigo Akademia Indonesia, 2021)
This study discussed mangrove ecotourism based on Sanak Sedagho, namely ecotourism management based on local wisdom. The management of sanak sedagho is novelty finding in the management of mangrove ecosystems. The mangrove ecotourism in Sungai Apit Sub-district is not active, while the Mangrove Sungai Bersejarah (MSB) Ecotourism still survives, it is still visited and as meeting place at the sub-district and district levels. This study is an ethnographic, where the researcher lived for two months in Sungai Ara Permai Village. The data were taken through library studies, internet, observation, participation observation, informal discussion and in-depth interviews. The main informants in this study are the initiators and managers of MSB Ecotourism and other informants who are community members and workers in MSB Ecotourism. This study found that the management of ecotourism based on local wisdom, in this case the sanak sedagho, is the key to the success of MSB Ecotourism being able survived even in the era of the covid 19 pandemic. This study contributes to the field of economic anthropology, especially in ecotourism management.